The logic of financial nationalism : the challenges of cooperation and the role of international law / Federico Lupo-Pasini. - Lupo-Pasini, Federico (Cambridge University Press, 2017)
Using case studies ranging from cross-border bank resolution to sovereign debt, the author analyzes the role of international law in protecting financial sovereignty, and the risks for the global financial system posed by the lack of international cooperation. Despite the post-crisis reforms, the global financial system is still mainly based on a logic of financial nationalism. International financial law plays a major role in this regard as it still focuses more on the protection of national interests rather than the promotion of global objectives. This is an inefficient approach because it encourages bad domestic governance and reduces capital mobility. In this analysis, Lupo-Pasini discusses some of the alternatives (such as the European Banking Union, Regulatory Passports, and international financial courts), and offers a new vision for the role of international law in maintaining and fostering global financial stability. In doing so, he fills a void in the law and economics literature, and puts forward a solution to tackle the problems of international cooperation in finance based on the use of international law.